Urbanización y cuencas hidrográficas en la Región Metropolitana de Buenos Aires, Argentina. Aportes desde el paisaje fluvial - Rotger, Daniela (2025)
The Metropolitan Region of Buenos Aires (RMBA) is the main urban conglomerate of the Argentine Republic. It is configured as a semicircular territory developed around the Autonomous City of Buenos Aires (CABA), whose diameter rests on the estuary of the Río de la Plata. The rivers and streams that flow into it are arranged in radial bands, forming geographical features that are decisive for urbanisation. The historical relationship between watershed’s system and the population process has been the subject of various environmental conflicts. The purpose of this article is to make visible the interactions between nature and urbanisation in the RMBA, taking watersheds as units of analysis, and the landscape as a theoretical and methodological approach. Two representative cases are analysed: del Gato stream basin, the most urbanised in the La Plata district (capital of the province of Buenos Aires), and El Pescado stream basin, the only watercourse of its kind to be designated as a protected landscape of provincial interest, whose urbanisation process is recent, yet accelerated. Methodologically, a comparative study has been carried out using a qualitative-quantitative approach based on a methodology for the valuation of river landscape previously developed for watersheds in the RMBA. The results of the research refer to the analysis of the physical-natural, historical-territorial and symbolic-cultural aspects of river landscape. The main conclusions analyse the impact that the valuation of the landscape could have on the territorial planning of regional watersheds.